Context and competition in the capture of visual attention - Hickey, Clayton (Springer-Verlag, 2011)
Competition-based models of visual attention propose that perceptual ambiguity is resolved through inhibition, which is stronger when objects share a greater number of neural receptive fields (RFs). According to this theory, the misallocation of attention to a salient distractor—that is, the capture of attention—can be indexed in RF-scaled interference costs. We used this pattern to investigate distractor-related costs in visual search across several manipulations of temporal context. Distractor costs are generally larger under circumstances in which the distractor can be defined by features that have recently characterised the target, suggesting that capture occurs in these trials. However, our results show that search for a target in the presence of a salient distractor also produces RF-scaled costs when the features defining the target and distractor do not vary from trial to trial. Contextual differences in distractor costs appear to reflect something other than capture, perhaps a qualitative difference in the type of attentional mechanism deployed to the distractor.